Psychological examinations in occupational health services: Legal regulations. Part II - Małgorzata Waszkowska; Agata Wężyk (Nofer Institute of Occupational Medicine, 2018)
This paper constitutes a continuation of the critical analysis of legal aspects of psychological examinations in some group of workers. In this part the appeal procedure, documentation, costs of examinations and supervision are discussed. The analysis has shown many deficiencies in regulations related to all aspects of psychological examinations. They arise from incoherence of legal regulations and the lack of regulations of some questions. This legal standing is restricted to occupational work and adversely affects the quality of supplied services. Therefore acts of law and regulations relevant to psychological examinations for the purpose of fitness-to-work certification need necessary adjustments. According to authors it is desirable to end the legal procedure amending the act of law on a profession of psychology and the self-government of psychologists, as well as to develop and implement executive regulations. Med Pr 2018;69(6):673-684